Performance and damage evolution of plain and fibre-reinforced segmental concrete pipelines subjected to transverse permanent ground displacement. Issue 2 (1st February 2018) - Pour-Ghaz, Mohammad; Wilson, Jacob; Spragg, Robert; Nadukuru, Srinivasa (Sid) S.; Kim, Junhee; O'Connor, Sean M.; Byrne, Edward M.; Sigurdardottir, Dorotea H.; Yao, Yao; Michalowski, Radoslaw L.; Lynch, Jerome P.; Green, Russell A.; et al.
Abstract: This paper presents the results of three full-scale experiments performed on segmental concrete pipelines subjected to permanent ground displacement. The first pipeline was made of reinforced concrete pipes and the second pipeline was made of steel fibre-reinforced concrete pipes. The third pipeline was made of a combination of fibre-reinforced and reinforced concrete pipes. An array of sensing techniques was used to assess the damage evolution in pipelines and their overall performance. Three stages of damage were observed. In the first stage, damage was concentrated in the joints near the fault line. In the second stage, the damage occurred in all joints along the pipeline. While in the first two stages damage was mainly concentrated at the bell and spigot joints of the pipe segments, the third stage of damage was characterised by severe damage and rupture of the body of pipe segments located in the immediate vicinity of the fault line. The modes of failure for the plain and fibre-reinforced concrete pipelines were similar in the first and second stages of damage. However, in the pipeline constructed using both plain and fibre-reinforced concrete pipe segments, the damage was concentrated in the standard reinforced concrete pipe segments.